Effect of dietary fat on serum parameters, and productive and reproductive performance of multiparous sows = Efecto de los lípidos de la dieta sobre parámetros séricos y desempeño productivo y reproductivo en cerdas multíparas - Rivas, Francisco G.; Gonzalez, Maria De Los Angeles; Matiller, Valentina; Williams, Sara I. (Facultad de Ciencias Veterinarias, Universidad Nacional del Litoral, 2024)
The objective of the study was to evaluate the effect of fat inclusion on the productive and reproductive parameters of sows and their litters as well as the serum concentrations of insulin, glucose, luteinizing hormone (LH) and non-esterified fatty acids (NEFAs). Thirty multiparous sows were divided into three groups (n=10) and randomly assigned to treatments T0, T1 and T2, corresponding to gestation and lactation diets with 0%, 3.5%, and 7% of fat inclusion, respectively. Blood samples were obtained from the jugular vein the day of weaning and on days 3, 5, and 7 after. The variables recorded were the sow average daily feed intake (ADFI), average daily energy intake (ADEI), body weight loss, litter size, survival rate, and litter average daily gain (ADG), litter weight at birth and weaning and the wean-to-estrus interval (WEI). Analyses were performed using the MIXED procedure of SAS (SAS Inst. Inc., Cary, NC). Fat inclusion improved the ADFI and ADEI of sows, and the piglet ADG. The WEI was reduced by 0.7 days in those sows supplemented with fat compared to the control group. Glucose, LH and insulin levels were not altered between treatments. However, NEFAs levels were higher in those sows consuming diets with no fat added.